2017
DOI: 10.4236/ce.2017.812124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Behavior Modification on Social Anxiety for High School Students

Abstract: The authors of this study adopted an approach from cognitive behavior modification to design a SMART strategy, and applied the intervention to high school students. This study used a multiple baseline across-subject design to measure the degree of social anxiety among three high school students for the duration of 3 to 5 weeks, and then used the SMART strategy to intervene and document their mastering of strategies and changes of social anxiety for 15 weeks. Their anxiety level was measured and recorded 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In the literature review, no study was found that investigated the effect of cognitive-behavior modification training on depressive symptoms among students. However, the results of this study agree with the findings of Arian and Dehghani Firoozabadi [29], Lotfi et al [27], Esmaili [30], Kazemian [28], Sadipoor et al [25], and Chen et al [26], confirming that the mental health has a significant relationship with negative self-talk, and teaching how to reduce negative self-talk is very effective in psychological adjustment. Arian and Dehghani Firoozabadi [29] showed that teaching positive self-talk is effective in increasing women's belief in their general self-efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the literature review, no study was found that investigated the effect of cognitive-behavior modification training on depressive symptoms among students. However, the results of this study agree with the findings of Arian and Dehghani Firoozabadi [29], Lotfi et al [27], Esmaili [30], Kazemian [28], Sadipoor et al [25], and Chen et al [26], confirming that the mental health has a significant relationship with negative self-talk, and teaching how to reduce negative self-talk is very effective in psychological adjustment. Arian and Dehghani Firoozabadi [29] showed that teaching positive self-talk is effective in increasing women's belief in their general self-efficacy.…”
Section: Discussionsupporting
confidence: 91%
“…Saadipoor et al [25] believed that teaching positive self-talk and eliminating cognitive errors and familiarity with the techniques of replacing negative self-talk with positive self-talk affect people's self-efficacy and their belief in mastery and success in various fields. Chen et al [26] observed that students' social anxiety decreased rapidly and significantly after intervention with cognitive-behavior modification strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of anxiety in several contexts of previous studies has been successfully studied and developed through the integration of several required sensors [9,10]. The overall research foundation tends to view conventional counseling strategies as generally emphasizing self-reporting of anxiety measurements with the capacity of counselors and counselees full of limitations and various perspectives of meaning [11]. The complexity of an anxiety condition experienced by a person requires detailed and comprehensive measurements so that the intervention given has the right level of targets and targets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the teacher's personality also provides social support and strengthens students' abilities [32]. In contrast, a teacher's lousy personality could also negatively impact the students' attitudes, behavior, appearance, and habit [25], [33].…”
Section: Introductionmentioning
confidence: 99%